PENGEMBANGAN METODE PEMBELAJARAN VIDEO BASED LEARNING BERBASIS VIDEO ANIMASI UNTUK MENINGKATKAN KETERAMPILAN SHOLAT SISWA KELAS VII DI SEKOLAH MTS DARUL AMIN - Norhidayani Norhidayani; Alamsyah Alamsyah; Abdul Azis; Anita Rahmayani (CV. ADIBA AISHA AMIRA, 2024)
The use of learning media is very necessary to help teachers in delivering material in class, moreover digital learning media is quite good to use because it adapts to the current era which is the era of digital use. This study aims to improve students' skills in the procedures for good and correct prayer. The research method used by the researcher is the RnD development method, with the Four-D Model (Define, Design, Develop, and Disseminate). Data collection techniques are carried out by means of interviews, observations, trials and evaluations (participants fill out questionnaires and assess animated videos that researchers make). The questionnaire was filled out by 24 people in class VII C. From the results of interviews with fiqh subject teachers, it was found that there were still many students, especially students in class VII C MTS Darul Amin, who did not know the correct and proper prayer movements, therefore the researcher is interested in developing digital learning media that can help fiqh subject teachers to deliver material about prayer in more detail, in addition to making it easier for students to access via video. So the results of the development made by the researcher are, students are more helped by the existence of learning videos about prayer procedures that can be accessed via gadgets, and participants understand more about prayer movements because the video has provided clear and detailed movements, with this, it can improve students' prayer procedure skills.